2019
DOI: 10.4314/jasem.v23i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Patterns and Multiple Antibiotic Resistance Index of <i>Salmonella species</i> Isolated from Waste Dumps in Zaria Metropolis, Nigeria

Abstract: Several items containing residual antimicrobial agents are disposed of in dumpsites, placing a pressure on the microbial flora and a potential for development of resistance in these microorganisms. Multidrug resistance patterns and multiple antibiotic resistance index of Salmonella spp. isolated from waste dumps in Zaria Metropolis were thus assayed in this study using one hundred and twelve (112) soil samples collected from four waste dumpsites located in Sabon-Gari, Samaru, Tudun-Wada and Zaria City. Salmone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…It is also indicative of the possible transfer of resistant genes via exchange of genetic materials (plasmids) among the microbial populations in dumpsite soils. A possible indication is the indiscriminate and high use of antibiotics among Abraka residents which corroborates reports of Nyandjou et al (2019). The implication of these findings is a possible spread of persistent and "difficult to cure" bacterial infections among the resident population.…”
Section: Discussionsupporting
confidence: 82%
“…It is also indicative of the possible transfer of resistant genes via exchange of genetic materials (plasmids) among the microbial populations in dumpsite soils. A possible indication is the indiscriminate and high use of antibiotics among Abraka residents which corroborates reports of Nyandjou et al (2019). The implication of these findings is a possible spread of persistent and "difficult to cure" bacterial infections among the resident population.…”
Section: Discussionsupporting
confidence: 82%
“…To overcome this limitation, we estimated the MARI values. In resource poor countries, where molecular analysis is not feasible, MARI is being used as a simple cost effective tool to track the source or indicate prior exposure to the tested antibiotics [29,30]. In this study, the MARI was higher than 0.2, indicating prior exposure to antibiotics.…”
Section: Discussionmentioning
confidence: 72%
“…In resource-poor settings, where all bacterial isolates are not subjected to the entire range of antibiotics and access to genomic analysis is poor, the multiple antibiotic resistance Index (MARI) can be used as an effective tool to determine the intensity of antibiotic resistance and to predict the previous exposure to tested antibiotics. In this study, MARI was derived from a ratio of the number of isolates found to have antibiotic resistance against the total number of antibiotics tested for that isolate [15,29,30]. A MARI value of more than 0.2 indicates the risk of high exposure to antibiotics in the poultry.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…This makes it an ideal place for the growth of vast array of bacteria, both pathogenic and nonpathogenic [32]. [30,31].…”
Section: Fig-4: Histogram Showing Indications For Oral and Dental Promentioning
confidence: 99%